POTRET IDEAL RELASI SUAMI ISTRI (Telaah Pemikiran Hadith Shaikh Nawawi Al-Bantani) - Surahmat (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2015)
Nawawi is a leading fi gure in the corners of the Islamic world. His work is monumental include Uqud al - lujain book, which describes the ideal portrait of the relationship between husband and wife in the ark undergoing households. In this study described the analysis of the traditions about the duty of the husband to the wife, the wife to the husband’s obligations, the primacy of prayer in the home for women and a ban on men looked at another woman ( not a mahram ). Many traditions that are not described by Nawawi quality, so as to maintain the originality Hadith red thread can be taken; if an authentic hadith sanadnya uncertain say there is a history that explains Thus, instead of words of the Prophet